The effect of tendency to globalization on mental health, (Case Study: Students of Shahid Chamran University) - Karim Rezadoust; Alihossein Hosseinzadeh; Hamidreza Nasrollahi Ghale Abde Shahi (توسعه اجتماعی, 2020)
The aim of this article is survey tendency to globalization on mental health. Theoretical basis of this article is the Giddens structure theory and risky society Ulrich Beck.The population in this article are 16409 students studying in theShahid Chamran University that was selected 377 person with the method stratified sampling proportional with size (gender, college and education) and according to table Krejcie and Morgan and to ensure that number rose to 400. In order to collect data is standardized questionnaires. Collected data were analyzed using the software SPSS and was used from Pearson's correlation coefficient and multivariate regression. Research findings argues that seen the significant positive correlation between social and economic trend of globalization with students' mental health and there is a significant inverse relationship between political and cultural trend of globalization with students'mental health. According to the regression equation only two variables social and cultural trend of globalization explained 0.111 of mental health variance. In a survey of demographic variables with students' mental was found that there is a significant positive correlation among income and socio-economic base with mental health. Also found that there is a significant difference average mental health in between men and women and workers and the unemployed but does not show a significant difference between singles and married.